(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the correlation between leg muscle power and smash skills in STKIP PGRI Bangkalan students. The background of this study is based on the importance of the role of leg muscle explosive strength in supporting the ability to smash in volleyball games. This study uses a quantitative approach with a correlational method. The research subjects amounted to 24 students. Data were collected through a leg muscle power test using a vertical jump and a smash skill test. The results showed a significant relationship between leg muscle power and smash skills. Students with high leg muscle power tend to have better smash skills compared to students who have low leg muscle power. This finding confirms that leg muscle power is one of the important factors in supporting the effectiveness of smash in volleyball. Therefore, coaches and physical education lecturers are advised to provide a special training portion to increase leg muscle power as part of a program to improve volleyball playing skills.